Commemorative plaque at the Town Hall - Ghosh, Ayan (2023)
Commemorative plaque at the Town Hall, dedicated to Colonel Thomas Cowper and Captain Charles Waddington of the Bombay Engineers. Work started in 1821, however, the original architect, Thomas Cowper died midway and Major John Hawkins came to be entrusted with the completion of the remaining building, which was finished in 1833.